Ayurveda and environmental network: Antimicrobial, pharmacological and ecological potential of Swietenia macrophylla Meliaceae (L.) Jacq. - Dawkar, Vishal; Chalwade, Anand (Biota, 2023)
To encapsulate the research reports on Swietenia macrophylla compounds to explore their medicinal and ecological importance. The plants of Swietenia genus may be used to recover ecological aspects and importantly to develop drugs to cure many diseases. Many research articles reported through the work that S. macrophylla possesses antidiabetic, antioxidative and antihyperlipidemic activity, antimicrobial and pharmacology potential to ecological recovery property. Herbal drugs prepared from plant extracts have an enormous range of medicinal properties. S. macrophylla species ascertained to have a broad range of medicinal properties and ecological potential to reap up beneficial things. Swietenia macrophylla Meliaceae (L.) Jacq. have immune-modulatory, anticancer, anti-diabetic, antiviral, anti-hypertension and many other curative properties. S. macrophylla gorgeous in flavonoids, tannins, alkaloids, sugars and terpenoids and limonoids, is believed to have vast therapeutic potential. Mahogany can grow in perennial and seasonally dry areas and even flourish in various types of soils. Encapsulation of the research reports on Swietenia macrophylla compounds is essential to explore their medicinal and ecological importance. The plants of Swietenia genus may be used to recover ecological aspects and importantly to develop drugs to cure many diseases. However, more study is needed to categorize, describe and systematize the vital metabolites and plant extracts used in disease treatment. Abundance of limonoids and many other compounds in Swietenia genus brand this plant more noteworthy for in-depth molecular level studies to discover additional potential about its pharmacological, ecological and other possible possessions.